Entorne social y la manifestación del trastorno oposicionista desafiante en los niños de la Escuela de Educación Básica Espíritu Santo - Macias Cisneros, Naila Betzabeth (2019)
The present investigation has a psychosocial approach, why it has been developed with the purpose of attending to all the social and psychological problems that present the students of the School of Basic Education "Espíritu Santo" and that are generating inadequate behaviors inside and outside the classroom. The purpose is to diminish the manifestations of oppositional defiant disorder that can generate violence and increase the coexistence between children in the short term and within the community in the long term, so it was started from the improvement of the skills of the compression of conflicts, communication, its social environment and in itself know how to solve their own problems. Additionally, it will help in the modification and improvement of attitudes and values of self-esteem, tolerance, tolerance, diversity, respect, responsibility, cooperation and participation. These skills, attitudes and peaceful values highlight the fundamental role of the relationships that the child establishes with friends, family members, peers; thus allowing a better coexistence and better personal and social development. The lack of cooperation, which is very important for personal, family and community development, demonstrates the need to investigate the social environment surrounding the adolescent, shows the need for this research; The key to this is to try to resolve any type of conflict that the child finds in his environment, being aware that conflicts will always be present, however.